English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

equation:
( (1) / (x-1) ) + ( (3) / (x+1) ) = ( (4) / (x^2 - 1) )

i know the first step is to divide by the common denominator,
which is (x+1)(x-1), but after that i'm at a lost...thanks for the help, really appreciate it.

2006-10-29 13:17:49 · 2 answers · asked by shih rips 6 in Science & Mathematics Mathematics

2 answers

1. Multiply out common denominator:
-> (1/(x-1) + 3/(x+1))(x+1)(x-1) = (x+1)(x-1)(4)/(x^2-1)
-> (x+1) + 3(x-1) = 4
2. Expand brackets and solve:
-> x + 1 + 3x - 3 = 4
-> 4x - 2 = 4
-> 4x = 4 + 2 = 6
-> 4x = 6
-> x = 6/4
-> x = 1.5

2006-10-29 13:22:23 · answer #1 · answered by turkeyphant 3 · 0 0

1/(x-1) + 3/(x+1) = 4/(x^2-1)

(x+1)/(x-1)(x+1) + 3(x-1)/(x+1)(x-1) = 4/(x+1)(x-1)

x+1 + 3(x-1) = 4
4x -2 = 4
x = 1.5

2006-10-29 13:20:44 · answer #2 · answered by buaya123 3 · 0 1

fedest.com, questions and answers